(untitled) (Bulletin of criminological association of Ukraine, 2025)
The article briefly outlines: the main preventive measures to prevent offenses implemented by law enforcement agencies, objects of prevention and subjects of preventive measures; the opinions of legislators and the views of lawyers of the past. The content of the main levels of crime prevention, individual crime prevention measures, types of individual preventive measures, and groups of crime prevention subjects are considered. The state of criminological prevention at the national level is analyzed. Proposals were made regarding the development of regulatory legal acts aimed at organizing and implementing state policy on preventing and combating crime.